Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the value of [tex]\( x \)[/tex] for which [tex]\( (f - g)(x) = 0 \)[/tex], we first need to set up the expression for [tex]\( (f - g)(x) \)[/tex].
Given:
[tex]\[ f(x) = 16x - 30 \][/tex]
[tex]\[ g(x) = 14x - 6 \][/tex]
The function [tex]\( (f - g)(x) \)[/tex] is:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
Substitute the given functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] into the above expression:
[tex]\[ (f - g)(x) = (16x - 30) - (14x - 6) \][/tex]
Now, simplify the equation by combining like terms:
[tex]\[ (f - g)(x) = 16x - 30 - 14x + 6 \][/tex]
[tex]\[ (f - g)(x) = (16x - 14x) + (-30 + 6) \][/tex]
[tex]\[ (f - g)(x) = 2x - 24 \][/tex]
We need to find the value of [tex]\( x \)[/tex] for which [tex]\( (f - g)(x) = 0 \)[/tex], so set [tex]\( 2x - 24 = 0 \)[/tex] and solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 24 = 0 \][/tex]
[tex]\[ 2x = 24 \][/tex]
[tex]\[ x = \frac{24}{2} \][/tex]
[tex]\[ x = 12 \][/tex]
The value of [tex]\( x \)[/tex] that satisfies [tex]\( (f - g)(x) = 0 \)[/tex] is:
[tex]\[ \boxed{12} \][/tex]
Given:
[tex]\[ f(x) = 16x - 30 \][/tex]
[tex]\[ g(x) = 14x - 6 \][/tex]
The function [tex]\( (f - g)(x) \)[/tex] is:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
Substitute the given functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] into the above expression:
[tex]\[ (f - g)(x) = (16x - 30) - (14x - 6) \][/tex]
Now, simplify the equation by combining like terms:
[tex]\[ (f - g)(x) = 16x - 30 - 14x + 6 \][/tex]
[tex]\[ (f - g)(x) = (16x - 14x) + (-30 + 6) \][/tex]
[tex]\[ (f - g)(x) = 2x - 24 \][/tex]
We need to find the value of [tex]\( x \)[/tex] for which [tex]\( (f - g)(x) = 0 \)[/tex], so set [tex]\( 2x - 24 = 0 \)[/tex] and solve for [tex]\( x \)[/tex]:
[tex]\[ 2x - 24 = 0 \][/tex]
[tex]\[ 2x = 24 \][/tex]
[tex]\[ x = \frac{24}{2} \][/tex]
[tex]\[ x = 12 \][/tex]
The value of [tex]\( x \)[/tex] that satisfies [tex]\( (f - g)(x) = 0 \)[/tex] is:
[tex]\[ \boxed{12} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.